Allocating collaborative costs in multimodal barge networks for freight bundling. (December 2017) - Ramaekers, Katrien; Verdonck, Lotte; Caris, An; Meers, Dries; Macharis, Cathy
Abstract: In order to improve the competitive position and efficiency level of multimodal transport, consolidation of freight flows is often suggested. Bundling networks require cooperation between multiple partners in the multimodal transport chain. In this context, the question rises how benefits may be allocated fairly among the spatially distributed participants in the cooperation. A great deal of scientific literature reports on the behavior of allocation methods in collaborations between shippers or carriers making use of unimodal road transport. However, research on cost or savings allocation methods in multimodal transport is scarce. The main contribution of this paper is thus to provide a first insight in the complexity of sharing cost savings fairly among shippers who bundle freight flows in order to reach economies of scale in multimodal barge transport. By applying four different allocation methods to two realistic case studies, a comparison is made between simple and straightforward allocation mechanisms and more advanced techniques based on cooperative game theory. Special attention is paid to the savings division among coalition partners and collaborative stability. Results demonstrate the influence of cooperation characteristics on allocation outcomes and underline the value of carefully selecting appropriate allocation mechanisms when long-term stability of the multimodal barge collaboration is aspired.